The Book Heritage of the Scriptoriums in Kazan and Sviyazhsk of the XVII Century - A. I. Makarov (Библиосфера)
The political and cultural integration of the vast Kazan region, annexed to the Moscow state in the middle of the XVI century, led to the formation of the Russian regional cultural environment and the organization of the Orthodox mission. The important factor in these processes was the distribution of Cyrillic handwritten and printed books. Kazan and Sviyazhsk became the centers of Russian book culture in the annexed lands, where monasteries and temples with rich libraries had already existed since the second half of the XVI century. The purpose of this study was to identify and characterize the products of the book-writing (Cyrillic) workshops of Kazan and Sviyazhsk of the XVII century. The article provides information about 24 manuscripts, including illuminated ones, identified in catalogs and collections of various scientific libraries, their content, scientific, religious and cultural significance. The names of professional scribes and drawing-artists who worked in Kazan, the names of the owners of the manuscripts are established. Summarizing the information on the identified manuscripts allows us coming to the conclusion about the systematic books rewriting in Kazan already at the beginning of the XVII century, to put forward assumptions about the existence of a bishop’s library, about the presence of book-rewriting workshops in the Kazan Zilant Uspensky and Trinity Feodorovsky monasteries and in the Sviyazhsky Trinity monastery